2018
DOI: 10.1108/acmm-01-2017-1750
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rare earth lanthanum-cerium doping on corrosion behavior of zinc-aluminum-magnesium hot-dip galvanizing coatings used for transmission towers

Abstract: Purpose-The purpose of this study is to improve the corrosion resistance of the transmission towers by Zinc-aluminum-magnesium (Zn-Al-Mg) coatings doped with rare earths lanthanum (La) and cerium (Ce) (denoted as Zn-Al-Mg-Re) in Q345 steel. Design/methodology/approach-The phase structure of Zn-Al-Mg-Re composite coatings has been determined by X-ray diffraction, whereas their surface morphology and cross-sectional microstructure as well as cross-sectional elemental composition have been analyzed by scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Therefore, during the wear process, a loose and cracked oxide layer on the surface of ZK60 alloy can be easily fractured [38]. On the other hand, several studies [39][40][41] reported that Ce in Mg-alloys could increase the resistance to the oxidation of Mg-alloy. The addition of Ce to Mgalloys leads to formation of a protective and compact oxide layer on the surface during the wear process.…”
Section: Wear Mechanismsmentioning
confidence: 99%
“…Therefore, during the wear process, a loose and cracked oxide layer on the surface of ZK60 alloy can be easily fractured [38]. On the other hand, several studies [39][40][41] reported that Ce in Mg-alloys could increase the resistance to the oxidation of Mg-alloy. The addition of Ce to Mgalloys leads to formation of a protective and compact oxide layer on the surface during the wear process.…”
Section: Wear Mechanismsmentioning
confidence: 99%
“…A deposition of Ce3+ and Ce4+ phases improved the corrosion resistance of the metal. Hot dip galvanizing coating of Lanthanum (La) and cerium (Ce) on Q345 steel was developed by Han et al [25]. The result exhibited the development of new phase such as LaAl3 and Al11Ce3.…”
Section: Rare Earth Coating On Steel and Metalsmentioning
confidence: 99%